Radiation protection to workers and public in general, in installations that use industrial radioisotopes (2013)
This paper verifies the fulfilment that the dose rates in the surroundings of an installation that operates radioisotopes for industrial use with activities of at least 50 Ci. If it also meets the requirements established by the International Protocols for Radiation Protection for workers and public in general. In this particular case, it was validated the installation of nuclear radiations labs at Universidad Pedagógica y Tecnológica de Colombia. The procedure was based in the construction of the geometry of the installation code MCNPX, detectors were placed at various points within and outside the installation, which allowed calculating photon fluency that cross the different containment barriers designed for this purpose. Using the respective conversion factors established by the International Commission of Radiological Protection (ICRP-74, 1997) for fluency conversion to dose which were achieved through calculating the different dose rates at these points, which were compared with experimental measurements. The results confirm that the installation meets the requirements for radiation protection and the most importantly fact is that some prevention tips were recommended.